Liver infiltrating mononuclear cells in children with type 1 autoimmune hepatitis. Issue 4 (17th February 2006) - De Biasio, M B; Periolo, N; Avagnina, A; García de Dávila, M T; Ciocca, M; Goñi, J; de Matteo, E; Galoppo, C; Cañero-Velasco, M C; Fainboim, H; Muñoz, A E; Fainboim, L; et al.
Abstract : Objective: To investigate infiltrating cells in the liver of children with type 1 autoimmune hepatitis (AH-1). Methods: liver biopsies from 24 untreated AH-1 patients (14 children, 10 adults), five patients with hepatitis C virus related chronic hepatitis (HCV), and 10 control liver specimens (CL) were processed for immunohistochemical cell characterisation. Results: Two different cell distribution patterns were detected in the liver of patients with AH-1: (1) CD4 + and CD20 + cells were found in the central areas of the portal tracts (portal distribution); (2) CD8 + cells were observed at the periphery of the portal space (periportal distribution). Some cell subsets, like CD56, CD57, Fas-L, and Bak, showed a non-defined distribution pattern. The presence of two well defined patterns of cell distribution was not observed in HCV and CL (CD4 +, CD20 +, and CD8 + cells were uniformly distributed in the portal space). In AH-1 and CL, the NK markers CD56 and CD57 were found scattered throughout the liver parenchyma. However, in HCV biopsies, CD56 + cells were also clearly increased in both the portal and the periportal areas. Biopsies of AH-1 and HCV patients showed a uniform distribution of Fas-L and Bak in the portal and periportal areas, with Bak staining also detected in the hepatic parenchyma. Conclusions: Despite clinical and genetic differences, there was a similar distribution of liver infiltrating mononuclear cells in children and adults with AH-1. These results raise the possibility of reclassifying cryptogenic chronic hepatitis by immunohistochemical analysis of infiltrating liver cells.